The railway theme on the Web of Science database: a panel of scientific literature with bibliometric indicators - Lourenço, Cátia de Sousa; Silva, Luiz Carlos da; Miguel, Marcelo Calderari; Moraes, Margarete Farias de; Costa, Rosa da Penha Ferreira da (Informação em Pauta, 2022)
The railways, in Brazil, are an expression of tradition and modernity, they appear to be new spaces for tourism and sociability, accommodating debates on aspects of memory, the silencing of public power, the path of technological prosperity. The research thus seeks to situate the space and the scientific path that involves the railroad path in the thematic scope of Information Science. The indexing terms relevant to this sphere are analyzed in the WoS database. The diagnosis places indicators, evidence and metrics on the bibliographic portfolio, that is, the historical and social context of scientific production. The objective is to probe the memory and the railway heritage and verify the quantity of published articles; list the scientific journals that most promote this theme; establish which facts of representativeness of the theme in the time frame from 2001 to 2021. The result recalls that the importance of railroads to transit in different areas, treading various paths and constructs that accommodate relevant approaches within the scope of Social Memory, applied to the archival, in the regarding the review and strengthening of policies, as well as strengthening the vision and legacy of the humanist horizon.